Sequence Determinants Spanning −10 Motif and Spacer Region Implicated in Unique Ehrlichia chaffeensis Sigma 32-Dependent Promoter Activity of dnaK Gene - Liu, Huitao; Ganta, Roman R. (Frontiers in Microbiology, 2019)
Ehrlichia chaffeensis is an obligate intracellular tick-borne bacterium that causes human monocytic ehrlichiosis. Studying Ehrlichia gene regulation is challenge, as this and related rickettsiales lack natural plasmids and mutagenesis experiments are of a limited scope. E. chaffeensis contains only two sigma factors, σ32 and σ70. We previously developed E. coli surrogate system to study transcriptional regulation from RNA polymerase (RNAP) containing Ehrlichia σ32 or σ70. We reported that RNAP binding motifs of E. chaffeensis genes recognized by σ32 or σ70 share extensive homology and that transcription may be initiated by either one of the sigma factors, although transcriptional efficiencies differ. In the current study, we investigated mapping the E. chaffeensis dnaK gene promoter using the pathogen σ32 expressed in E. coli lacking its native σ32. The E. coli surrogate system and our previously described in vitro transcription system aided in defining the unique -10 motif and spacer sequence of the dnaK promoter. We also mapped σ32 amino acids/domains engaged in its promoter regulation in E. chaffeensis. The data reported in this study demonstrate that the -10 and -35 motifs and spacer sequence located between the two motifs of dnaK promoter are critical for the RNAP function. Further, we mapped the importance of all six nucleotide positions of the -10 motif and identified critical determinants within it. In addition, we reported that the lack of C-rich sequence upstream to the -10 motif is unique in driving the pathogen-specific transcription by its σ32 from dnaK gene promoter. This is the first study in defining an E. chaffeensis σ32-dependent promoter and it offers insights about how this and other related rickettsial pathogens regulate stress response genes.